(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
In this paper, A 23 year old married woman who was diagnosed as a case of giant condyloma acuminatum of vulva measuring about 15 x 8 x 3 cm, irregular surface with multiple projections, oval in shape, firm to hard in consistency, mildly tender, exophytic, cauliflower like growth involving the whole vulva (lower part of mons pubis, labia, vestibule, clitoris, around vaginal opening). Another multiple small lesions were present at perineal region but there was no inguinal lymphadenopathy. She underwent a combined electro cauterization and cryotherapy for small to moderate size multiple primary and recurrent warty lesions and wide surgical excision with fasciocutaneous advancement flaps procedure for a giant lesions in the vulva. Excisional biopsies were performed to detect potential malignancy but malignancy was not found histologically. The patient was advised to first follow-up 1 month after operation when multiple small warty lesions were developed and treated and the subsequent follow-ups for 3 months.